A patient with X‐linked dyskeratosis congenita presenting with bronchiolitis obliterans requiring lung transplantation and immunodeficiency1. Issue 1 (19th March 2012) - Goldfarb, Samuel; Sullivan, Kathleen E.; Jyonouchi, Soma
Abstract Dyskeratosis congenita (DKC) is a syndrome characterized by immunodeficiency, bone marrow (BM) failure, somatic abnormalities, and predisposition to malignancy, resulting from mutations in proteins involved in maintenance of telomeres. Pulmonary fibrosis resulting in respiratory failure is a serious complication affecting approximately 20% of DKC patients. Pediatric pulmonologists should consider this diagnosis in patients with lung fibrosis and concurrent immunodeficiency or BM failure. Pediatr Pulmonol. 2013; 48:91–93. © 2012 Wiley Periodicals, Inc.